Pengaruh jogging sebagai aktivitas fisik terhadap fungsi kognitif siswa sekolah dasar - Altamimi, Jidan Maulidin; Afianti Sulastri; Sehabudin Salasa (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Physical activity plays a major role in enhancing children’s physical and cognitive development. Jogging, as a simple form of aerobic exercise, is believed to improve concentration, attention, and executive function, which greatly influence the learning abilities of elementary school students. This study aimed to determine the effect of jogging on cognitive function among elementary school students. The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. A total of 68 students from SDN Sukasirna 03, Bogor Regency, participated as subjects and underwent a jogging intervention three times per week for four weeks, with each session lasting 30 minutes. Cognitive function was measured using the Grid Concentration Exercise Test (GCET) and the Stroop Color and Word Test (SCWT). Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in cognitive function after the jogging intervention (GCET: Z = –7.162, p < 0.001; SCWT: Z = –4.067, p < 0.001). These findings indicate that jogging effectively enhances concentration, attention, and executive function in elementary school students. Physiologically, aerobic exercise such as jogging improves cerebral blood circulation and stimulates the release of brain-derived neurotrophic factor (BDNF), which supports synaptic plasticity, working memory, and cognitive flexibility. Therefore, regular jogging is recommended as a simple and effective strategy to support children’s cognitive development and academic performance.